A new education environment: cybertext and hypertext - Kikhney, Lyubov G.; Pavlova, Tatiana L.; Gavrikov, Vitaliy A.; Merkel, Elena V. (Opción, 2019)
A new technological paradigm, having replaced postmodernism in the judgment of many researchers, is considered in the article. The changes in scientific and pedagogical understanding of the literary process and media are shown through comparative research methodology. It is stated that there is no unity in terms of describing the new paradigm in science (in particular in English-language sources). Correspondingly, there is no consistency between the different concepts of the new paradigm, approaches to hypertextuality, cybertextuality, etc. In here, the first important step towards understanding the situation "after postmodern" would be the developing authentic concepts.